Bibliometric analysis of cancer research outputs in Botswana between 2009 and 2021. (March 2023) - Koobotse, Moses O.; Zachariah, Matshediso; Senabye, Bonolo; Gobe, Irene; Kadimo, Khutsafalo; Nthontho, Keneuoe C.; Mokomane, Margaret; Koto, Garesego; Phuthego, Thato; Lekgetho, Henry; Ndlovu, Andrew; Motswaledi, Modisa; et al.
Abstract: Introduction: Cancer research is critical for cancer control policies; however, the state of cancer research activities in Botswana is largely unknown. The goal of this review was to describe trends and patterns of cancer research outputs in Botswana. Methods: PubMed, Web of Science, EBSCOhost, African Journals Online, and African Index Medicus databases were systematically searched for peer-reviewed, primary cancer-related research articles published on the Botswana population or by Botswana institutions between January 2009 and June 2021. Results: Of the 86 publications included, 39 (45 %) were about cervical cancer, followed by breast cancer (10 %) and Kaposi sarcoma (7 %). The remainder (27 %) were not focused on any specific cancer type. The research activities were skewed towards three main areas of scientific interest: early detection, diagnosis, and prognosis; cancer control, survivorship, and outcomes; and treatment. Botswana was represented by authors in the first (54 %), last (53 %), and any authorship (53 %) positions. The United States of America had the strongest collaborative partnerships with Botswana, followed by the United Kingdom and South Africa. The majority of funding institutions were American (76 %) and the National Institutes of Health was the most mentioned funding organization, accounting for 33 % of all financial acknowledgments. Only 9 % of the funding acknowledgments came from Botswana. Conclusion and policy summary: Although cancer research in Botswana is expanding because of substantial foreign assistance, it is also hampered by a lack of local funding, minimal participation by Botswana-affiliated researchers, and research that is not aligned with disease burden. Our study highlights the need to strengthen local research capacity in Botswana. Highlights: Cervical cancer, breast cancer and Kaposi sarcoma were the most researched types of cancer in Botswana from 2009 to 2021. Authors affiliated to institutions in Botswana represented approximately half of all authors during the review period. Strongest collaborative cancer research partnerships were with US institutions. Cancer research in Botswana was mostly aided by foreign funders with limited local funding.